Integrert behandling av rus og psykiske lidelser i en sikkerhetspsykiatrisk avdeling: Evaluering av implementeringstiltak - Bjørnstad, Kari E.; Gråwe, Rolf W. (Nordisk tidsskrift for helseforskning, 2014)
Integrated treatment of substance abuse and mental illness in a security psychiatric ward: Evaluation of the implementation measures Violence and homicide among patients with severe mental disorders is associated with substance use. The main aim of this study was to improve organization-level dual diagnoses capability in a forensic psychiatric unit. Health personnel and organization level assessments were performed before and after program and staff training and program implementation. Results: The DDCMHT targeted important areas of change and staff training was associated with an increased total score in dual diagnoses capability from 2.7 to 3.9 on a 1-5 scale, a change from being categorized as Addiction or Mental health Services Only to Dual Diagnosis Capable. Important implementation factors were clinical experience and organizational support. Despite implementation challenges, the main conclusion to be drawn from the study is that improvements in dual diagnoses capability are feasible at a service level.
Keywords: Substance use; severe mental disorders; implementation; treatment; forensic; ruslidelse; alvorlig psykisk lidelse; kvalitetsforbedring; implementering; integrert behandling; sikkerhetspsykiatri.